Closed versus open lateral internal anal sphincterotomy in a chronic anal fissure - B. N., Anandaravi; B., Ramaswami (International Surgery Journal, 2017)
Background: Anal fissure is a common proctological problem, which presents with pain in the anal region during and after defecation. The aim of the study was to determine the best technique for surgical treatment of chronic anal fissure patients. Methods: The study was designed as a prospective randomized study. The study was conducted in surgical unit, K.R. Hospital, MMCRI, Mysore, India from January 2015 to June 2016. A total of 100 patients undergoing surgery were divided into two groups. In group A there were 50 patients who were treated by closed lateral internal anal sphincterotomy, and in group B there were 50 patients who were managed by open lateral internal anal sphincterotomy method. Patients were followed up for 6 months following surgery to observe for pain, bleeding, infection, incontinence, and recurrence. The exclusion criteria were patients who had in addition haemorrhoids or any other anorectal diseases. Results: There was acceptable difference in postoperative acute complications between the two methods of internal anal sphincterotomy. However, in group A, three patients (6%) versus 10 (20%) were complicated with incontinence postoperatively, whereas the recurrence rate was 4 versus 4% in group A versus group B, respectively (P = 0.015). Conclusions: There was significant difference between closed and open methods of lateral internal sphincterotomy in recurrence rate, healing rate, and other complications. Closed lateral internal sphincterotomy is treatment of choice for chronic anal fissure and can be done effectively and safely with acceptable rate of complications. Our recommendations are that closed technique should be adopted by experienced surgeons and Trainee should be initially trained by open technique then be shifted to closed technique.